2018
DOI: 10.1519/jsc.0000000000002071
|View full text |Cite
|
Sign up to set email alerts
|

Positional Anthropometric and Performance Profile of Elite Gaelic Football Players

Abstract: Shovlin, A, Roe, M, Malone, S, and Collins, K. Positional anthropometric and performance profile of elite gaelic football players. J Strength Cond Res 32(8): 2356-2362, 2018-The aim of the current investigation was to evaluate the variation in the anthropometric and performance characteristics of elite Gaelic football players with respect to position. One hundred forty-eight elite Gaelic footballers underwent anthropometric (height, body mass, sum of 7 skinfolds, and % adipose tissue) and performance (counter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 23 publications
4
27
0
1
Order By: Relevance
“…It has been reported that fitness levels 43 and physical match demands 44 in Gaelic football increase systematically across the season. The periodisation of training load will depend on the team's objectives for the year.…”
Section: The Game Model Approachmentioning
confidence: 99%
“…It has been reported that fitness levels 43 and physical match demands 44 in Gaelic football increase systematically across the season. The periodisation of training load will depend on the team's objectives for the year.…”
Section: The Game Model Approachmentioning
confidence: 99%
“…Although, similar to stature, non-significant positional variations regarding body mass have been reported [6]. Higher adiposity % has been observed in full forwards compared to the three middle positional lines [6]. Inconsistencies of anthropometric data between studies are evident within Gaelic football, and thus, the need for further analyses to gain a greater insight into the positional profile of the population.…”
Section: Introductionmentioning
confidence: 99%
“…An elite Gaelic footballer's height typically ranges 178-187 cm [4][5][6]. Midfielders are reported to be significantly taller compared to all other outfield positions [4], often followed by the goalkeeper [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En el deporte de elite durante los últimos años, las características antropométricas y la composición corporal asociadas al ren-dimiento deportivo han tomado una gran importancia (Henríquez-Olguín et al, 2013;Gale-Watts & Nevill, 2016). Diversas investigaciones han estudiado los perfiles antropométricos de distintos deportes, los cuales han logrado establecer características específicas que sirven como datos referenciales, permitiendo identificar las características de los deportistas en distintos niveles de rendimiento (Rienzi et al, 2000;Sánchez-Muñoz et al, 2007;Holway & Garavaglia, 2009;Chaabène et al, 2012;Vernillo et al, 2013;Erculj & Bracic, 2014;Rodriguez et al, 2014;Gutnik et al, 2015;Yáñez Sepúlveda et al, 2015;Bridge et al, 2016;Shovlin et al, 2018), en este escenario el estudio del somatotipo y la composición corporal cobra importancia, ya que cada especialidad deportiva presenta una serie de exigencias que obliga, en la mayoría de los casos, a poseer una determinada anatomía en los deportistas con el fin de lograr un desempeño deportivo óptimo (Rodríguez et al, 2014). Por ejemplo, en lo que respecta a las características específicas en el desarrollo del tenista, la altura es el determinante antropométrico principal de la velocidad de saque en jugadores profesionales (Bonato et al, 2015).…”
Section: Introductionunclassified